KINERJA PEGAWAI: PENGARUH KOMPETENSI, DISIPLIN DAN BEBAN KERJA YANG DI MEDIASI OLEH KEPUASAN - Yusri Yusri; Ilham Safar; Nurmadhani Fitri Suyuthi (Universitas Ichsan Sidenreng Rappang, 2026)
This study aims to examine and analyze the effect of competence, work discipline, and workload on employee performance, with job satisfaction serving as a mediating variable at the Public Appraisal Services Office (KJPP) Satria dan Rekan in Indonesia. This research adopts a quantitative approach. The total population comprises 130 employees (consisting of 75 appraisers and 55 administrative and finance staff) at KJPP Satria dan Rekan across Indonesia. The researcher designated the appraiser group as the primary focus of the study. Consequently, from the target population of 75 appraisers, a sample of 44 respondents was selected using a simple random sampling technique. Data were collected using Google Forms questionnaires evaluated on a Likert scale. Data analysis was executed using Variance-Based Structural Equation Modeling (SEM-PLS) facilitated by SmartPLS v.4.0 software. The results revealed that among the tested direct and indirect relationships Work discipline has a positive and significant direct effect on employee performance; Competence has a positive and significant direct effect on job satisfaction. Conversely, Competence and Workload do not significantly affect employee performance directly; Work discipline and Workload do not significantly impact job satisfaction; and Job satisfaction has no significant direct effect on employee performance. Furthermore, job satisfaction fails to mediate the relationships between competence, work discipline, or workload and employee performance at KJPP Satria dan Rekan in Indonesia.